Remotely characterizing photosynthetic biocrust in snowpack-fed microhabitats of Taylor Valley, Antarctica - Power, Sarah N.; Salvatore, Mark R.; Eric R. Sokol; Lee F. Stanish; Borges, Schuyler R.; Byron Adams; John E. Barrett (Science of Remote Sensing, 2024)
Microbial communities are the primary drivers of carbon cycling in the McMurdo Dry Valleys of Antarctica. Dense microbial mats, consisting mainly of photosynthetic cyanobacteria, occupy aquatic areas associated with streams and lakes. Other microbial communities also occur at lower densities as patchy surface biological soil crusts (hereafter, biocrusts) across the terrestrial landscape. Multispectral satellite data have been used to model microbial mat abundance in high-density areas like stream and lake margins, but no previous studies have investigated the lower detection limits of biocrusts. Here, we describe remote sensing and field-based survey and sampling approaches to study the detectability and distribution of biocrusts in the McMurdo Dry Valleys. Using a combination of multi- and hyperspectral tools and spectral linear unmixing, we modeled the abundances of biocrust in eastern Taylor Valley. Our spectral approaches can detect low masses of biocrust material in laboratory microcosms down to biocrust concentrations of 1% by mass. These techniques also distinguish the spectra of biocrust from both surface rock and mineral signatures from orbit. We found that biocrusts are present throughout the soils of eastern Taylor Valley and are associated with diverse underlying soil communities. The densest biocrust communities identified in this study had total organic carbon 5x greater than the content of typical arid soils. The most productive biocrusts were located downslope of melting snowpacks in unique soil ecosystems that are distinct from the surrounding arid landscape. There are similarities between the snowpack and stream sediment communities (high diversity of soil invertebrates) as well as their ecosystem properties (e.g., persistence of liquid water, high transfer of available nutrients, lower salinity from flushing) compared to the typical arid terrestrial ecosystem of the dry valleys. Our approach extends the capability of orbital remote sensing of photosynthetic communities out of the aquatic margins and into the drier soils which comprise most of this landscape. This interdisciplinary work is critical for measuring and monitoring terrestrial carbon stocks and predicting future ecosystem dynamics in this currently water-limited but increasingly dynamic Antarctic landscape, which is particularly climate-sensitive and difficult to access.
Keywords: Antarctica; biocrust; carbon; reflectance spectroscopy; snow; soil ecology

Estimating microbial mat biomass in the McMurdo Dry Valleys, Antarctica using satellite imagery and ground surveys - Power, Sarah N.; Salvatore, Mark R.; Eric R. Sokol; Lee F. Stanish; John E. Barrett (Polar Biology, 2020)
Cyanobacterial mat communities are the main drivers of primary productivity in the McMurdo Dry Valleys, Antarctica. These microbial communities form laminar mats on desert pavement surfaces adjacent to glacial meltwater streams, ponds, and lakes. The low-density nature of these communities and their patchy distribution make assessments of distribution, biomass, and productivity challenging. We used satellite imagery coupled with in situ surveying, imaging, and sampling to systematically estimate microbial mat biomass in selected wetland regions in Taylor Valley, Antarctica. On January 19th, 2018, the WorldView-2 multispectral satellite acquired an image of our study areas, where we surveyed and sampled seven 100 m2 plots of microbial mats for percent ground cover, ash-free dry mass (AFDM), and pigment content (chlorophyll-a, carotenoids, and scytonemin). Multispectral analyses revealed spectral signatures consistent with photosynthetic activity (relatively strong reflection at near-infrared wavelengths and relatively strong absorption at visible wavelengths), with average normalized difference vegetation index (NDVI) values of 0.09 to 0.28. Strong correlations of microbial mat ground cover (R2 = 0.84), biomass (R2 = 0.74), chlorophyll-a content (R2 = 0.65), and scytonemin content (R2 = 0.98) with logit transformed NDVI values demonstrate that satellite imagery can detect both the presence of microbial mats and their key biological properties. Using the NDVI—biomass correlation we developed, we estimate carbon (C) stocks of 21,715 kg (14.7 g C m−2) in the Canada Glacier Antarctic Specially Protected Area, with an upper and lower limit of 74,871 and 6312 kg of C, respectively.
Keywords: Antarctica; microbial mat; multispectral imagery; NDVI; Nostocales; remote sensing

Evaluating alternative metacommunity hypotheses for diatoms in the McMurdo Dry Valleys using simulations and remote sensing data - Eric R. Sokol; John E. Barrett; Tyler J. Kohler; Diane M. McKnight; Salvatore, Mark R.; Lee F. Stanish (Frontiers in Ecology and Evolution, 2020)
Diatoms are diverse and widespread freshwater Eukaryotes that make excellent microbial subjects for addressing questions in metacommunity ecology. In the McMurdo Dry Valleys of Antarctica, the simple trophic structure of glacier-fed streams provides an ideal outdoor laboratory where well-described diatom assemblages are found within two cyanobacterial mat types, which occupy different habitats and vary in coverage within and among streams. Specifically, black mats of Nostoc spp. occur in marginal wetted habitats, and orange mats (Oscillatoria spp. and Phormidium spp.) occur in areas of consistent stream flow. Despite their importance as bioindicators for changing environmental conditions, the role of dispersal in structuring dry valley diatom metacommunities remains unclear. Here, we use MCSim, a spatially explicit metacommunity simulation package for R, to test alternative hypotheses about the roles of dispersal and species sorting in maintaining the biodiversity of diatom assemblages residing in black and orange mats. The spatial distribution and patchiness of cyanobacterial mat habitats was characterized by remote imagery of the Lake Fryxell sub-catchment in Taylor Valley. The available species pool for diatom metacommunity simulation scenarios was informed by the Antarctic Freshwater Diatoms Database, maintained by the McMurdo Dry Valleys Long Term Ecological Research program. We used simulation outcomes to test the plausibility of alternative community assembly hypotheses to explain empirically observed patterns of freshwater diatom biodiversity in the long-term record. The most plausible simulation scenarios suggest species sorting by environmental filters, alone, was not sufficient to maintain biodiversity in the Fryxell Basin diatom metacommunity. The most plausible scenarios included either (1) neutral models with different immigration rates for diatoms in orange and black mats or (2) species sorting by a relatively weak environmental filter, such that dispersal dynamics also influenced diatom community assembly, but there was not such a strong disparity in immigration rates between mat types. The results point to the importance of dispersal for understanding current and future biodiversity patterns for diatoms in this ecosystem, and more generally, provide further evidence that metacommunity theory is a useful framework for testing hypotheses about microbial community assembly.
Keywords: Antarctica; Bacillariophyceae; dispersal; Nostoc; stream ecology